2018
DOI: 10.33005/jasf.v1i01.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rupiah Exchange Rate, GDP Growth, and Dow Jones Index on Composite Stock Price Index in Indonesia Stock Exchange

Abstract: A capital market is a meeting place for stock sellers and buyers with the aim of getting maximum profits. To get these benefits, investors need information about the stock price index. Factors that influence the Stock Price Index are important information for investors. The composite stock price index (CSPI) is one of the main indicators that reflects the performance of the capital market whether it is experiencing an increase or is experiencing a decline. These factors include the rupiah exchange rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
4
7
0
4
Order By: Relevance
“…And when the world gold price drops, many investors will sell their gold and switch to stocks so that the JCI will increase. This study is in accordance with another research conducted by Sartika (2017) and Oktavia, which shows the world gold price has a negative effect on the JCI (Oktavia et al, 2018;Sartika, 2017). However, this result is not in line with research that conducted by Haryanto & Astuti (2021), Anggriana (2020), andBasit (2019), which stated that there is no effect of the world gold price on the Composite Stock Price Index (Anggriana & Paramita, 2020;Basit, 2020;Haryanto & Astuti, 2021).…”
Section: Figure-3: Normality Test Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…And when the world gold price drops, many investors will sell their gold and switch to stocks so that the JCI will increase. This study is in accordance with another research conducted by Sartika (2017) and Oktavia, which shows the world gold price has a negative effect on the JCI (Oktavia et al, 2018;Sartika, 2017). However, this result is not in line with research that conducted by Haryanto & Astuti (2021), Anggriana (2020), andBasit (2019), which stated that there is no effect of the world gold price on the Composite Stock Price Index (Anggriana & Paramita, 2020;Basit, 2020;Haryanto & Astuti, 2021).…”
Section: Figure-3: Normality Test Resultssupporting
confidence: 93%
“…Because stock trading on the IDX tends to be dominated by stock trading in the mining area, the price increase of these mining stocks will eventually trigger an increase in the JCI. This state is in line with research results conducted by Beureukat & Andriani (2021), Novianti &Perwati (2020), andOktavia et al, (2018) which also shows that world oil prices partially have a significant and positive effect on the JCI (Beureukat & Andriyani, 2021;Novianti & Perwati, 2019;Oktavia et al, 2018). However, this is not the same with research conducted by Anggriana & Paramita (2020), Dewi, Sartika (2017), Fuad & Yuliadi (2021), and Hersugondo, which states that world oil prices do not have any effect on the Jakarta Composite Index (JCI) (Anggriana & Paramita, 2020;Dewi, 2020;Fuad & Yuliadi, 2021;Hersugondo et al, 2019;Sartika, 2017).…”
Section: The World Oil Prices Effect On the Composite Stock Price Ind...supporting
confidence: 93%
See 2 more Smart Citations
“…Information asymmetry models based on the asymmetric information problem between issuing firms and underwriters, investors and underwriters, issuers and investors, and informed and uninformed investors; institutional explanations for IPO under-pricing has inspired the emergence of three dominant institutionalbased theories, including lawsuit avoidance, price stabilization, and tax advantages hypotheses; ownership and control theories contend that IPO under-pricing works as an effective mechanism in shaping the shareholder base to deter outside investors from intervening in managing their firms once they are publicly listed; and the last theory was the presence of informational cascades as a behavioural explanation, which is discussed where the central argument is that the IPO market is prone to the presence of "irrational" investors who bid up the price of IPO shares beyond their true value (Jamaani & Alidarous, 2019). Several previous studies related to phenomena under-pricing is according to (Akseptori et al, 2019) concluded that internal factors (Debt To Equity Ratio (DER), Earning Per Share (EPS), Return On Assets (ROA), Company Age (AGE), Company Size (SIZE), Percentage of Shares Offered (PSD) has a significant effect on under-pricing and stock performance, while external factors (Inflation (INF), Exchange Rate (KURS), Bank Indonesia Interest Rates (RATE) have no significant effect on under-pricing and stock performance in companies conducting IPOs in the Indonesia Stock Exchange in the infrastructure, utility, and transportation sector in 2010-2018, which in line with (Oktavia & Handayani, 2018) that the rupiah exchange rate does not affect the Composite Stock Price Index (CSPI). Yusniar, (2016) shows that the performance of shares in companies that conducted IPOs in 2010 -2012 for the short and long term is significantly different.…”
Section: Figure 1 the Number Of Companies Conducting Ipos Based On Industrial Sectorssupporting
confidence: 59%